Pengembangan Blog Sebagai Media Pembelajaran Matematika - Nugroho, Aji Arif; Putra, Rizki Wahyu Yunian; Putra, Fredi Ganda; Syazali, Muhamad (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
This study aims to test the feasibility of media-based learning Blog in learning mathematics on trigonometric subjects. This development research uses 8 stages from 10 stages of borg and gall method that are potential and problem, data collection, product design, product validation, product revision, product test, product revision and mass production. Learning media blogs are developed with the help of adobe flash which aims to provide some animation. This research was conducted in SMA Negeri 1 Batanghari class X students. The assessment instrument used was questionnaire of feasibility test by media expert, Expert of Material, and Questionnaire of student response. The results of the research are: 1) Based on the validation of material expert judgments obtained an average score of 4.65 is located in the category of